2018
DOI: 10.3390/catal8120673
|View full text |Cite
|
Sign up to set email alerts
|

Application of Catalytic Wet Peroxide Oxidation for Industrial and Urban Wastewater Treatment: A Review

Abstract: Catalytic wet peroxide oxidation (CWPO) is emerging as an advanced oxidation process (AOP) of significant promise, which is mainly due to its efficiency for the decomposition of recalcitrant organic compounds in industrial and urban wastewaters and relatively low operating costs. In current study, we have systemised and critically discussed the feasibility of CWPO for industrial and urban wastewater treatment. More specifically, types of catalysts the effect of pH, temperature, and hydrogen peroxide concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…On the other hand, the removal of TN in the NAP-HW sample was only about 5%, while for NAP-SW and NAP-WWTP matrices it was slightly higher, at 20% and 30%, respectively (Figure 10b). From the obtained results, it could be concluded that the organic matter present in the HW and WWTP samples can act as a scavenger of • OH radicals in the CWPO reaction [47].…”
Section: Catalytic Wet Peroxide Oxidation In Different Real-aqueous Mmentioning
confidence: 87%
See 1 more Smart Citation
“…On the other hand, the removal of TN in the NAP-HW sample was only about 5%, while for NAP-SW and NAP-WWTP matrices it was slightly higher, at 20% and 30%, respectively (Figure 10b). From the obtained results, it could be concluded that the organic matter present in the HW and WWTP samples can act as a scavenger of • OH radicals in the CWPO reaction [47].…”
Section: Catalytic Wet Peroxide Oxidation In Different Real-aqueous Mmentioning
confidence: 87%
“…So, it could be suggested that the extra recalcitrant organic matter attributed to the micropollutant had a detrimental effect on the degradation of the aromatic compounds, if the dose of H 2 O 2 in excess referred to the stoichiometric amount. So, it could be concluded that the more recalcitrant or complex organic matter consumes an important amount of H 2 O 2 in the CWPO reaction before the removal of the more readily degradable organic matter occurs [47].…”
Section: Catalytic Wet Peroxide Oxidation In Different Real-aqueous Mmentioning
confidence: 99%
“…The recent development of structured catalysts/reactors using monolith [21][22][23] or structured cellular foams [24,25] has circumvented the barrier to scaling up. Besides, a variety of agro-food effluents i.e., from coffee [26], olive oil mills [27][28][29] and wineries [30], and industrial effluents, i.e., from textile [31], pharmaceutical [32], cosmetic [33] and chemical production [34][35][36], have been suitable treated by this technology. More recently, it has also been demonstrated to be a feasible technique to reduce the impact of residual contaminants, such as persistent endocrine-disrupting chemicals [36], present in very low concentrations in urban wastewater, or antibiotics and other pharmaceuticals in sanitary wastewater [37][38][39].…”
Section: Of 17mentioning
confidence: 99%
“…Despite the potential offered by CWPO, which can be exploited to treat industrial and domestic wastewater before or after a biological treatment within a wide range of pollutant loads [4,36] with a simple installation, since conventional atmospheric pressure reactors may be used, there are no commercial CWPO processes with solid catalysts. This work serves to help translate CWPO research into an industrial reality.…”
Section: Of 17mentioning
confidence: 99%
“…This special issue gives an overview of the state-of-the-art CWPO research for the treatment of industrial and urban wastewaters and how this process can be integrated into the water treatment process [1]. It is illustrated that the high versatility of this low-cost technology, thanks to the CWPO operational flexibility, is easily adaptable to any kind of wastewater, either polluted by high-loaded recalcitrant organics in industrial wastewaters or by emerging pollutants at micro-concentration levels in urban waters., This versatility also stands on the application of different types of solid catalysts, which can be tailored according to the process requirements.…”
mentioning
confidence: 99%